CROCHET WALLET MAKING TRAINING FOR TEACHERS AND PAUD STUDENTS BAMBIM BAITUL MUTTAQIEN PAUD KEBONLEGA SUB-DISTRICT BOJONGLOA KIDUL CITY BANDUNG - Rizkiah, Riza; Luciana, luciana; Nurherawati, Feny; Pravitasari, Filly (Inaba of Community Services Journal, 2023)
Handmade art encompasses various forms of handicraft art created by humans, including knitting. Knitting is a needlework activity that utilizes thread and hook needles. It encompasses different techniques such as embroidery, weaving, crocheting, and knitting itself. Additional activities like lacework, quilting, embroidery, needlepoint, and rugs are also considered part of the knitting realm. Although knitting and crochet are sometimes used interchangeably, they have distinct meanings. Crochet can be created using either manual or mechanical methods, employing a special hook needle to create desired shapes by hooking the thread under the previous loops. Crochet work is known for its textured appearance, with the texture varying depending on the stitches used. Examples of crochet stitches include chains, single crochet, half double crochet, double crochet, treble crochet, double trebles, slip stitch, blocks, picots, cross stitch, clusters, knots stitch, and popcorn stitch.